Case Report of an Endovascular Repair of a Residual Type A Dissection Using a Not CE Not FDA-Approved Najuta Thoracic Stent Graft System. Issue 3 (January 2015) - Mangialardi, N.; Ronchey, S.; Malaj, A.; Lachat, M.; Serrao, E.; Alberti, V.; Fazzini, S.; Leischik., Roman
<x xml:space="preserve">Abstract</x> Abstract This report describes an endovascular repair of a residual type A dissection using a medical device that is not marked by european conformity (CE) or Food and Drug Administration (FDA). The patient underwent ascending aortic surgery for acute type A dissection. The 2-year angio–computed tomography demonstrated patency of the residual false lumen with evolution into a 6 cm aneurysm, the extension of the dissection from the aortic arch to the aortic bifurcation with thrombosis of the right common iliac artery. There was no CE- or FDA-marked medical device indicated for this case or any other acceptable therapeutic alternative. We used the Najuta thoracic stent graft and successfully handled the pathology in a multiple-phase treatment. Technology is evolving with specific grafts for the ascending and fenestrated grafts for the aortic arch. In this single case the Najuta endograft, in spite of the periprocedural problems, was a valid therapeutic option.